Eﬀect of naftalenacetic acid and 6-bencilaminopurine in the induction of embriogenic calllus of Carica papaya L. var. criolla - Gonzales-Zavaleta, Osmar (2018)
The papaya (Carica papaya L.), Caricaceae, is an important crop for its high nutritional value and its medicinal and industrial applications, however, this crop has problems of pests and diseases, which requires research to obtain improved varieties of papaya. An alternative is the cultivation of anthers for which it is necessary to know their competence with the induction of calluses; with the stated objective of this experience was to determine the effect of naphthaleneacetic acid and 6-benzylaminopurine in the induction of embryogenic calluses in anthers of C. papaya L. var. criolla.  The obtained buds were measured and grouped according to their length, to determine the state of development of the pollen grain and the microspore state was confirmed with the coloring of acetic carmine and HCl. Then the explants were subjected to a cold pretreatment (6 ° C) for 4 days, then they were seeded in the Murashige & Skoog medium, which contained sucrose (3%), phytagel (0.5%), pH 6.0 and combinations of ANA and BAP at ppm concentrations. The evaluation was performed during 4 months, the treatment T4 (ANA 1 and BAP 0.5) was the best for the percentage of anthers with calluses (up to 40%), as for microspores induced the best was T5 (ANA 1 and BAP 1 ) with 2.9%. The size of the anthers increased and the color of the anthers changed from yellow to brown. During the induction process, embryos were not observed, but tissue dedifferentiation (meristemoids) was observed.